EXISTENTIALIST FEMINISM OF “WOMEN’S SITUATION” IN PARK JOON-HWA’S BECAUSE THIS IS MY FIRST LIFE - Silani, Putri Anifa Surya (STBA Prayoga Padang, 2023)
Abstract Existentialist feminism is the idea of women being able to express themselves freely in both personal and social activities without being haunted by their existence as women. This can be seen in one of Simone de Beauvoir's concepts,